2022
DOI: 10.1177/20503121211068725
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure status of HIV-positive children and associated factors among children in public health facilities in East Arsi zone, Oromia regional state, South Eastern Ethiopia: A cross-sectional study

Abstract: Objectives: This study aims to assess the disclosure status of HIV-positive children and its associated factors in selected hospitals in East Arsi zone, Oromia regional state, Ethiopia, 2020. Methods: Institutional-based cross-sectional study design was conducted on 410 sample size. Four hospitals were randomly selected among hospitals that currently gave service. Data were collected from caregivers/biological parents by interviewing from 30 July 2020 to 30 August 2020 using the systematic random sampling tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Age for disclosure was consistent throughout our study's quantitative and qualitative components, demonstrating that parents preferred to tell their children they had HIV when above 12 years. In a similar pattern, Yami et al reported that thirty-ve per cent of caregivers mentioned that the reason to disclose HIV status to children is when a child is a mature enough age greater than 12 years (19). In addition, a higher percentage of disclosure was also found in a study by Vreeman et al, which states that older children were more likely to be aware of their status than younger children, possibly because of increased maturity, independence, and self-care responsibilities (20) .…”
Section: Discussionmentioning
confidence: 84%
“…Age for disclosure was consistent throughout our study's quantitative and qualitative components, demonstrating that parents preferred to tell their children they had HIV when above 12 years. In a similar pattern, Yami et al reported that thirty-ve per cent of caregivers mentioned that the reason to disclose HIV status to children is when a child is a mature enough age greater than 12 years (19). In addition, a higher percentage of disclosure was also found in a study by Vreeman et al, which states that older children were more likely to be aware of their status than younger children, possibly because of increased maturity, independence, and self-care responsibilities (20) .…”
Section: Discussionmentioning
confidence: 84%
“… 10 The possible reason is attributed to an insufficient knowledge and skill to approach their HIV-positive children, as well as fear of discrimination and stigma, by families, friends and neighbors. 27 It is possible that health care providers are unsure of how to handle disclosure.…”
Section: Discussionmentioning
confidence: 99%